Transcriptome analysis of endometrial tissues following GnRH agonist treatment in a mouse adenomyosis model - Guo S; Lu X; Gu R; Zhang D; Sun Y; Feng Y (Dove Medical Press, 2017)
Song Guo,1,* Xiaowei Lu,1,* Ruihuan Gu,2 Di Zhang,3 Yijuan Sun,2 Yun Feng1 1Department of Obstetrics and Gynecology, Reproductive Medicine Center, Ruijin Hospital Affiliated to Shanghai Jiaotong University School of Medicine, Shanghai, People’s Republic of China; 2Gynecology, Shanghai Ji Ai Genetics & In Vitro Fertilization Institute, Obstetrics and Gynecology Hospital, Fudan University, Shanghai, People’s Republic of China; 3Department of Gynecology and Obstetrics, Jinan Military General Hospital, Jinan, People’s Republic of China *These authors contributed equally to this work Purpose: Adenomyosis is a common, benign gynecological condition of the female reproductive tract characterized by heavy menstrual bleeding and dysmenorrhea. Gonadotropin-releasing hormone (GnRH) agonists are one of the medications used in adenomyosis treatment; however, their underlying mechanisms are poorly understood. Moreover, it is difficult to obtain endometrial samples from women undergoing such treatment. To overcome this, we generated an adenomyosis mouse model, which we treated with an GnRH agonist to determine its effect on pregnancy outcomes. We also analyzed endometrial gene expression following GnRH agonist treatment to determine the mechanisms that may affect pregnancy outcome in individuals with adenomyosis.Methods: Neonatal female mice were divided into a control group, an untreated adenomyosis group, and an adenomyosis group treated with a GnRH agonist (n=6 each). The pregnancy outcome was observed and compared among the groups. Then, three randomly chosen transcriptomes from endometrial tissues from day 4 of pregnancy were analyzed between the adenomyosis group and the GnRH agonist treatment group by RNA sequencing and quantitative reverse transcription polymerase chain reaction (PCR).Results: The litter size was significantly smaller in the adenomyosis group than in the control group (7±0.28 vs 11±0.26; P<0.05). However, the average live litter size was increased (10±0.28 vs 7±0.28; P<0.05) after GnRH agonist treatment. Three hundred and fifty-nine genes were differentially expressed in the GnRH agonist-treated group compared with the untreated group (218 were downregulated and 141 were upregulated). Differentially expressed genes were related to diverse biological processes, including estrogen metabolism, cell cycle, and metabolite biosynthesis.Conclusion: GnRH agonist treatment appears to improve the pregnancy outcome of adenomyosis in a mouse model. Besides pituitary down-regulation, other possible mechanisms such as the regulation of cell proliferation may play a role in this. These new insights into GnRH agonist mechanisms will be useful for future adenomyosis treatment. Keywords: adenomyosis, GnRH agonist, mouse, RNA-seq, pregnancy outcome